2011
DOI: 10.1021/ol102992n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Allenephosphoramide and Its Utility in the Preparation of 4,9-Dihydro-2H-benzo[f]isoindoles

Abstract: Allenephosphoramides were prepared from propargyl alcohols and diethyl arylphosphoramides using Yb(OTf)(3) as catalyst. In the presence of iodine, 4,9-dihydro-2H-benzo[f]isoindole derivatives could be efficiently constructed from the same two starting materials in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…In 2010, Wang's group accomplished an efficient approach for the construction of 4,9‐dihydro‐2 H ‐benzo[ f ]isoindole derivatives 110 in good yields via iodine‐promoted cascade cyclization of tertiary propargylic alcohols 108 with diethyl arylphosphoramides 109 as nucleophiles under mild conditions (Scheme 41). [57] In this transformation, the key intermediate phosphoramide substituted allene was generated, and then reacted with another propargylic alcohols to give the target product 110 . Experimental results showed that the phosphoramide substituted allenes C are unstable and could be easily hydrolyzed.…”
Section: Reactions Involving N P‐nucleophiles To Capture Allenyl Carmentioning
confidence: 99%
“…In 2010, Wang's group accomplished an efficient approach for the construction of 4,9‐dihydro‐2 H ‐benzo[ f ]isoindole derivatives 110 in good yields via iodine‐promoted cascade cyclization of tertiary propargylic alcohols 108 with diethyl arylphosphoramides 109 as nucleophiles under mild conditions (Scheme 41). [57] In this transformation, the key intermediate phosphoramide substituted allene was generated, and then reacted with another propargylic alcohols to give the target product 110 . Experimental results showed that the phosphoramide substituted allenes C are unstable and could be easily hydrolyzed.…”
Section: Reactions Involving N P‐nucleophiles To Capture Allenyl Carmentioning
confidence: 99%
“…In the presence of iodine, 4,9-dihydro-2H-benzo[f]isoindole derivatives 141 could be efficiently constructed from propargyl alcohols and phosphoramides in the presence of iodine in a single step via ABB9 MCRs (Scheme 52). 117…”
Section: Synthesis Of 49-dihydro-2h-benzo[f]isoindolesmentioning
confidence: 99%
“…The allenes generated in situ could then undergo various cascade reactions to form many useful structural frameworks. [20][21][22][23][24][25][26] In a recent report, the Zhou group have developed an intramolecular Friedel-Crafts (IFC) reaction that provides a facile and versatile method for one-step construction Very recently, our group has reported the application of propargylic alcohols for the construction of substituted fluorenes, in which five-membered rings were constructed by IFC reactions. 29 It was envisaged that the similar IFC reaction of propargylic alcohols may also be applied to construct a five-membered heterocyclic skeleton.…”
Section: Introductionmentioning
confidence: 99%